Linkages nascent entrepreneurship and knowledge quality resonance: explore voluntary co-creation from service dominant logic - Moonti, Agustinus; Panjaitan, Roymon; Adam, Echan; Roslan, Astil Harli (Business: Theory and Practice, 2023)
This research aims to explore a new conceptual model capable of filling the research gap on the experience of nascent entrepreneurs and the quality of knowledge resonance, which centered on exploring voluntary co-creation of shared value. Data were obtained from the experience of 232 start-up multisectoral companies in Java Island, Indonesia.The findings of this study contribute empirically and practically to the knowledge needed to investigate the creation of shared value. The results showed that the direct impact experienced by nascent entrepreneurs is negatively correlated, while the relationship associated with quality resonance of knowledge to the performance of business innovation is positive. Secondly,the concept of the model is proven by the high willingness to explore voluntary co-creation from service-dominant logic to bridge the negative correlation gap of the experience of nascent entrepreneurs. Thirdly, the direct impact led to the voluntary creation of shared value complements with limitations on the dominant service logic of the optional co-production into a co-creation concept called value-in-use. This model instils an attitude on the importance of voluntary exploring co-creation of high nascent entrepreneur experience and the quality knowledge resonance.